Chromosomal Microarray Study in Prader-Willi Syndrome - Butler, Merlin G.; Hossain, Waheeda A.; Cowen, Neil; Bhatnagar, Anish (International journal of molecular sciences, 2023)
A high-resolution chromosome microarray analysis was performed on 154 consecutive individuals enrolled in the DESTINY PWS clinical trial for Prader-Willi syndrome (PWS). Of these 154 PWS individuals, 87 (56.5%) showed the typical 15q11-q13 deletion subtypes, 62 (40.3%) showed non-deletion maternal disomy 15 and five individuals (3.2%) had separate unexpected microarray findings. For example, one PWS male had Klinefelter syndrome with segmental isodisomy identified in both chromosomes 15 and X. Thirty-five (40.2%) of 87 individuals showed typical larger 15q11-q13 Type I deletion and 52 individuals (59.8%) showed typical smaller Type II deletion. Twenty-four (38.7%) of 62 PWS individuals showed microarray patterns indicating either maternal heterodisomy 15 subclass or a rare non-deletion (epimutation) imprinting center defect. Segmental isodisomy 15 was seen in 34 PWS subjects (54.8%) with 15q26.3, 15q14 and 15q26.1 bands most commonly involved and total isodisomy 15 seen in four individuals (6.5%). In summary, we report on PWS participants consecutively enrolled internationally in a single clinical trial with high-resolution chromosome microarray analysis to determine and describe an unbiased estimate of the frequencies and types of genetic defects and address potential at-risk genetic disorders in those with maternal disomy 15 subclasses in the largest PWS cohort studied to date.